Implementation of Good Governance Principles in the 2024 Election: A Study of Transparency and Accountability in the Central Maluku Regency KPU - Rahmi Rahmi; Normawati Normawati; Josep A Ufie; Safrudin Bustam Layn (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
This study analyzes the governance of the 2024 elections in terms of transparency and accountability of the Central Maluku Regency KPU. The results show that the governance of the 2024 elections in Central Maluku Regency, from the perspectives of transparency and accountability, can be described as follows. First, the implementation of the elections in Central Maluku Regency has shown a fairly good level of transparency. This is evident from the openness of information to the public, the involvement of various stakeholders, and the ease of public access to data and the processes of each stage of the elections. The Central Maluku Regency KPU has consistently applied the principle of openness from the stage of updating voter data and recruiting ad hoc bodies to the announcement and recapitulation of voting results. Second, the institutional accountability of the election organizers has been carried out in accordance with applicable regulations, through administrative, financial, and ethical accountability mechanisms supervised by internal and external supervisory bodies such as Bawaslu and DKPP. The performance of the KPU and Bawaslu also shows good synergy in monitoring stages and handling violations, although there are still obstacles in technical aspects, especially in reporting and the consistency of monitoring results documentation. However, strengthening is still needed in information systems, internal supervision, and the technical capacity of organizers in the field. Therefore, recommendations for improvement can be made to strengthen the governance of future elections by strengthening regulations and compliance, optimizing public information disclosure, improving human resource competencies, and strengthening participatory oversight and inter-agency collaboration.